Study On Nurses' Knowledge Regarding Some Medications Induce Congenital Malformations During Pregnancy: Studi Pengetahuan Perawat Mengenai Beberapa Obat yang Menyebabkan Cacat Bawaan Selama Kehamilan - Ali, Wasfi Dhahir Abid (Indonesian Journal on Health Science and Medicine, 2025)
Many of the medications used to treat psychological illnesses, antibiotics, and other treatments for pregnant women later appear to have negative effects on the fetus during pregnancy or birth, and some of them appear after different age periods. The current study aims to familiarize nurses with these medications because of their major role in preparing and administering medications, drug doses, and medication administration periods. Female and male nurses with different academic levels and years of experience in different hospital departments participated in the questionnaire for a group of medications that cause birth defects.  Most Participants have knowledge that induces birth defects or malformation during pregnancy especially medicines that are commonly used, also knowledge may correlate with their academic level or experience  Highlights: Nurses' knowledge of drugs causing birth defects during pregnancy. Awareness varies by academic level and work experience. Emphasizes nurses' role in safe medication administration. Keywords: Birth defects, Pregnancy medications, Nurse knowledge, Basra hospitals, Congenital malformations